Clima laboral en el Tecnicentro El Trueno en la cuidad de Babahoyo período 2023. - López Martínez, Ginger Gabriela (2025)
This research sought to evaluate the impact of the work environment on the operation of Tecnicentro el Trueno in the city of Babahoyo, evidence of questions that must be improved such as training, communication between employees, multidisciplinary work and motivation techniques, which will allow the work to meet expectations and obtain an affective work environment. This study classified as mixed qualitative-quantitative, it was necessary to resort to information from several authors, types and research methods such as: inductive, deductive and historical - logical method, to obtain the information techniques such as interview with the General Manager, Head of Inventory and Supervisor of the financial administrative department were used, in addition to surveys of employees belonging to the department, it was evaluated using Ishikawa's theory, work environment consolidation matrix and SWOT. The results show that the climate in the company is not ideal, which causes job dissatisfaction and failure to meet business objectives. There is a direct relationship between the work environment and the performance of the workers at Tecnicentro El Trueno in the city of Babahoyo, since an inadequate climate causes job dissatisfaction as well as failure to meet the stated objectives, thus altering the levels of emotional stability and performance of its workers.